Laboratory experiments in the system dynamics field (2012)
Controlled experiments, long used in psychology and economics, are increasingly being used to develop theories inthe areas of interest to management science, including decision making and systems. In this paper we review labora-tory experiments relating to system dynamics. We discuss how these experiments help to (1) determine causes forsubjects’ poor performance in dynamic environments and (2) model such behaviour in system dynamics models.Finally, we present the main insights from the works reviewed and propose some ideas for a research agenda.